Balloons in the Earth's Auroral Science—BALBOA's Modern Exploration. Issue 10 (6th October 2020) - Zhou, X.‐Y.; Rafol, S. B.; Michell, R. G.; Hampton, D.; Geach, C.; Berk, A.; Lummerzheim, D.; He, Y.‐T.
Abstract: Since 1892, when an aurora was first imaged by Martin Brendel, a German physicist, auroral forms and their dynamics have been acquired only when the aurora is in darkness. Due to the sunlight contamination from Rayleigh scattering, it has been a long‐term challenge of imaging sunlit aurora. In addition, other constraints exist, such as moonlight contamination, cloud occultation, and the limited land area available for installing imagers near the auroral zone in both hemispheres. While auroral imaging from space provides auroral global dynamics or small‐scale structures, depending on the spacecraft orbit, the image quality is affected by low spatial and temporal resolutions, sunlight, and the lack of traceability of auroral variations. Consequently, we have little knowledge of sunlit auroral forms and their dynamics, as well as their coupling to conjugate aurora. Given the fact that the solar wind‐magnetosphere‐ionosphere coupling is initiated on the dayside, understanding sunlit and dayside aurorae becomes very interesting and important. A scenario of imaging sunlit aurora from a balloon and the conceptual design of the instrument have been depicted in our previous article (Zhou et al., 2017, https://doi.org/10.1029/2006GL028611 ). This paper elaborates the new science enabled by this new means and the feasibility of auroral ballooning by showing some sunlit auroral images obtained from a balloon flight and calculations of the corresponding sky brightness. In addition, we describe and explain the most important specs of the new NIR camera‐head being developed for the BALBOA balloon mission that is currently supported by the NASA/Low Cost Access to Space program. Key Points: The dayside and sunlit aurorae are important for understanding the dayside and transient solar wind and magnetosphere coupling Observing auroral forms and dynamics in the sunlight from the balloon altitude is indisputably feasible A balloon payload for auroral imaging is under development